San José Pignatelli (1735-1811) y Vicente Requeno(1743-1811), socios de la Academia Clementina - Antonio ASTORGANO ABAJO (Cuadernos Dieciochistas)
RESUMEN: El objeto de este trabajo es trazar las relaciones de los jesuitas expulsos, san José Pignatelli (1735-1811) y Vicente Requeno (1743-1811), amantes de las Bellas Artes, con la Academia Clementina en la Bolonia de finales del siglo XVIII. ABSTRACT: The aim of this work is to trace the relationships between expelled Jesuits, Saint José Pignatelli (1735-1811) and Vicente Requeno (1743-1811), both Fine Arts lovers, and the Clementine Academy of Bologna at the end of the 18th century.